Reorientasi Ideologi Urban Sufism di Indonesia terhadap Relasi Guru dan Murid dalam Tradisi Generik Sufisme pada Majelis Shalawat Muhammad di Surabaya - Rubaidi, Rubaidi (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2015)
The article focuses on the discussion about ideology reorientation on Urban Sufism?s doctrines in Indonesia in the post Reformation Era. The study puts emphasis on Majelis Shalawat Muhammad and its teachings. The study on the doctrinal teachings based on practices (?amalîyah) of Majelis Shalawat Muhammad provides, on one hand, conceptual data on Sufism teachings within their generic meanings. On the other, it is intended to be a comparative study toward theoretical conceptions on Urban Sufism established by Julia Day Howell, Martin van Bruinessen, and other scholars on the field. This study underlines the relation of guru-murid (murshid and his pupils) in preserving doctrinal teachings and practices of Sufism, which have been uninterruptedly maintained from classical period until nowadays. Within the tradition of Sufism, the relation of guru-murid has generated a term what so-called walîy Allâh. Predicate as walîy Allâh within the personality of a pupil is indicated by his ability to reach and ?open? a dimension of tawhîd which is called mukâshafah. The dimension of mukâshafah has played a pivotal role in maintaining the transmission of teachings and doctrines of Sufism from generation to generation and ensuring their sustainability.